Environmental suitability and yield performance of pulse varieties in Northeastern region of Bangladesh: Pulse Performance in Northeastern Bangladesh (Journal of the Sylhet Agricultural University, 2026)
Pulses (Pisum sativum L.) are important grain legume crops that contribute significantly to Bangladesh's nutritional security as inexpensive, high-protein food sources. This research assessed the agronomic performance and environmental adaptability of four pea varieties (Pea Nator Local, Pea Jikorgacha Local, BARI Khesari-2, and BARI Motorshuti-3) at the experimental field of Sylhet AgriculturalUniversity during the 2019-2020 Rabi season. The experiment employed a Randomized Complete Block Design (RCBD) with four replications. The results showed significant variation among varieties for plant population, leaves plant⁻¹, branches plant⁻¹, plant height, fresh weight of plant, pods plant⁻¹, pod length, seeds pod⁻¹, 100 seeds weight, and seed yield. The results revealed that the highest seed yield was obtained from Natore local (1572.37 kg ha⁻¹) and it was similar to Jhikorgacha local (1440 kg ha⁻¹). The lowest seed yield was obtained from BARI motorshuti-3 (961.87 kg ha⁻¹). Environmental suitability analysis showed that Pea Nator local had perfect adaptation with 5.5% yield loss while BARI motorshuti-3 suffered 38.8% yield loss due to environmental stress. Above all Pea Nator local and Jikorgacha local may be suggested to farmers to cultivate in Sylhet.J. Sylhet Agril. Univ. 12(2): 77-86, 2025